Analisis Pemesanan Konsumen PT. Kepuh Kencana Arum Dengan Metode Root Cause Analysis - Kusuma, Yahya; Pulansari, Farida (LPPM Universitas Dharma Andalas, 2025)
Kepuh Kencana Arum is one of the leading manufacturing companies in the building materials sector, particularly products made of lightweight steel. However, in practice, PT. KKA faces several challenges in the SCM process that impact the company's operational efficiency, especially related to managing order status data. Root Cause Analysis (RCA) is a method used to solve problems by identifying the key factors that cause a problem or an undesirable event. Based on the available order data, the figures for August are 1,365,662 pcs, September 3,389,234 pcs, and October 3,989,930 pcs. In the production section, the figures for August are 1,066,229 pcs, September 2,985,195 pcs, and October 3,394,210 pcs. In August, the recorded shipment total was 931,446 pcs, which then increased significantly in September to 2,715,996 pcs, and continued to grow in October to 3,157,378 pcs.